Myxoma Atrium Kiri dengan Regurgitasi Trikuspid: Patofisiologi, Diagnosis dan Tata Laksana - Prima Almazini; Bambang Budi Siswanto; Nani Hersunarti; Rarsari Soerarso; Amiliana M Soesanto (Jurnal Kardiologi Indonesia, 2015)
Cardiac myxomas are the most common primary cardiac tumors. Myxoma are more common in women. Clinical manifestations can mimic many cardiac and noncardiac conditions. Transthoracic echocardiography (TTE) is the gold standard method in the diagnosis of cardiac myxoma. The management of cardiac myxoma are medical therapy for the treatment of associated conditions and surgical removal as the definitive treatment.